Production of Energy from Biomass: Near or Distant Future Prospects? - Goryunov A. G. Aleksey Germanovich; Goryunova N. N. Nataliya Nikolaevna; Ogunlana Ayodele Oludare; Manenti Flavio (2016, 2016)
Title screen